The importance of charged aerosols in the polar mesosphere in connection with Noctilucent Clouds and Polar Mesosphere Summer Echoes - Blix, Tom Arild (The Antarctic and Arctic Middle Atmospheres: Their Differences and Similarities, 1999)
A number of campaigns have been conducted in order to study Polar Mesosphere Summer Echos (PMSE) and Noctilucent Clouds (NLC) in the period 1991–1994. Several sounding rockets have been launched through these layers with measurements being performed on upleg as well as downleg. These include measurements of positive ions and electrons in both ram and wake positions, as well as measurements of charged aerosols in ram on upleg. In this paper we will review these measurements and make a preliminary classification of the data based upon the presence of PMSE and/or NLC. One of the mechanisms responsible for PMSE is the presence of neutral air turbulence in combination with a high Schmidt number. We will briefly discuss this type of echo using in situ rocket data. Differences and similarities of PMSE and NLC as observed both in the Arctic and the Antarctic will be discussed. Observations show that especially PMSE are much more frequent in the Arctic. This may be due to a difference in the water vapour content or the temperature at mesopause heights. Lack of data in the Antarctic makes it difficult to decide which of these two factors are the most important. More measurements, especially co-ordinated in situ and ground-based lidar and radar measurements, are needed to discuss the Arctic and Antarctic similarities and differences in further detail.
Keywords: Antarktis; astrofysikk; atmosfæren; geofysikk; mesosfæren; meteorologi; polarområdene

A global model tool for three-dimensional multiyear stratospheric chemistry simulations: Model description and first results - Rummukainen, Markku; Isaksen, Ivar S A; Rognerud, Bjørg; Stordal, Frode (Journal of Geophysical Research: Atmospheres, 1999)
The paper presents a new global modeling tool, Stratospheric Chemical Transport Model 2. It has been developed for effective three-dimensional multiyear stratospheric chemistry studies, featuring an extensive chemistry scheme, heterogeneous processing on sulfate aerosols, and some polar stratospheric cloud processes. The transport algorithm maintains sub-grid-scale distributions and connects vertically the stratospheric layers, even in a coarse vertical grid. The model has been integrated for 49 months, recycling 1 year of precalculated transport from a middle atmosphere general circulation model. One year of daily National Centers for Environmental Prediction global analyses are used as temperatures. Diurnal cycles of photolysis rates are recalculated every 7 days to give interaction with ozone changes. The model is able to describe most of the geographical and seasonal ozone variability and the meridional distributions of ozone, reactive nitrogen, chlorine, and bromine. Stratospheric diurnal cycles for nitrogen, hydrogen, chlorine, and bromine species are captured in detail. The upper stratosphere ozone deficiency, typical to models, is large. Its sensitivity to different ways of tuning are explored. Midlatitude, rather than polar, wintertime processes have so far been the focus in this model tool. The present transport and grid resolution are not suited for realistic simulations at high latitudes. As there is only a limited inclusion of polar stratospheric cloud (PSC) microphysics, chemical processing in the cold polar lower stratosphere also cannot be well simulated. For example, the Antarctic ozone hole is not simulated, but the modeled chemistry should be suitable for warm Arctic winters when type II PSCs and particle sedimentation do not occur.
Keywords: Antarktis; geofysikk; meteorologi; ozonlaget; polarområdene; stratosfæren; stratosfærisk kjemi

Large spatial variation in accumulation rate in Jutulstraumen ice stream, Dronning Maud Land, Antarctica - Melvold, Kjetil; Hagen, Jon Ove; Pinglot, Jean Francis; Gunuestrup, Niels (Annals of Glaciology, 1998)
A mass-balance programme was initiated on Jutulstraumen ice stream, western Dronning Maud Land,Antarctica, during the austral summer 1992-93. As a part of the mass-balance programme, accumulation rate was measured along the centre line of Jutulstraumen from the shelf edge up to the plateau at about 2500 m a.s.l. Accumulation distribution obtained from seven shallow firn cores and 48 slake readings is presented. The overall net accumulation trend displays a decreasing accumulation with increasing elevation and distance to coast, but on both the mesoscale and microscale there are significant variations. This is due to complex patterns of precipitation controlled by orography and redistribution by katabatic winds. The local accumulation distribution (few km scale) was found to be dependent on downslope surface gradient (aspect north, northwest), and variations up to 100% were found over distances of less than 3 km. The large variation in accumulation is important when selecting new core sites and for interpretation of temporal and spatial variations in accumulation derived from firn cores.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; geofysikk; geografi; glasiologi; isstrøm

Stability of the Thermohaline Circulation to Noisy Surface Buoyancy Forcing for the Present and a Warm Climate in an Ocean General Circulation Model - Skagseth, Øystein; Mork, Kjell Arne (Journal of Physical Oceanography, 1998)
The stabilities of two different circulation regimes in the North Atlantic, 1) the present thermohaline circulation and 2) a weaker thermohaline circulation, are compared using the Hamburg Large Scale Geostrophic (LSG) ocean circulation model. The latter circulation regime is obtained by restoring the LSG model toward an on average 48C warmer air surface temperature corresponding to a doubled atmospheric content of CO 2 . The stabilities of these stationary states are investigated by imposing various amounts of stochastic noise on the surface freshwater flux. The simulations show more variability on secular timescales for the present than for the warm climate. Since the modeled static stabilities for the two climates are relatively similar, the different rates of variability are probably connected to other mechanisms. In the present climate at high latitudes the two buoyancy fluxes due to heat and freshwater are of similar magnitudes but with opposite signs; thus switches between convective and nonconvective periods at secular timescales are possible. In the warm climate the buoyancy flux due to heat dominates. This compensates the effect of the noisy freshwater forcing and thus reduces the potential for secular oscillations. The stronger coupling between the Atlantic and the Southern Ocean for the present relative to the warm climate could also contribute to this difference. Furthermore, the simulations show that the variability of the Antarctic Circumpolar Current transport for the present climate exceeds that of the warm climate. For increasing stochastic noise the present circulation approaches that of the warm circulation. The authors apply a mixture of heat flux and temperature restoring for the surface boundary condition. Comparison with similar works, which apply a pure restoring for surface temperature, shows that the ocean circulation is much less sensitive to forced stochastic freshwater anomalies with the type of boundary condition used herein. A box model is used to illustrate the effects of the surface temperature parameterizations and the different buoyancy forcing for the present and warm climate.
Place: Boston MA, USA Publisher: American Meteorological Society
Keywords: AABW; Sørishavet; Sørishavsstrømmen; geofysikk; havstrømmer; oseanografi; polarområdene; vannmasser

Report of the Norwegian Antarctic Research Expedition 1992/93 - Orheim, Olav (ed.) (Norsk Polarinstitutt, 1997)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1992/93; ekspedisjoner; geofysikk; geologi; glasiologi; marin biologi; marin geologi; ornitologi; oseanografi; topografi

Spatial distribution of snow in western Dronning Maud Land, East Antarctica, mapped by a ground-based snow radar - Richardson, Cecilia; Aarholt, Eldar; Hamran, Svein-Erik; Holmlund, Per; Isaksson, Elisabeth (Journal of Geophysical Research: Solid Earth, 1997)
During the austral summer 1993/1994, the spatial distribution of snow was mapped by a ground-based snow radar (800–2300 MHz) in western Dronning Maud Land, East Antarctica. Snow radar soundings were performed along continuous profiles extending from the ice shelf up to the polar plateau, a total distance of 1040 km. The high-resolution radar registrations revealed subsurface layering in the uppermost 12 m of the snowpack. The travel time record was translated into snow accumulation expressed in water equivalents, based on an empirical relationship between wave speed and firn density. A good knowledge on snow density variations with depth is essential for the variability studies. Generally, the snow layering was well developed in the coastal area and less well developed on the polar plateau. High spatial variability in snow accumulation was observed on a regional as well as on a local scale. The variability was very high in areas with large surface slopes, such as the grounding zone and around nunataks. The highest variability was recorded in the nunatak area, where the standard deviation reached 59% of the spatial average accumulation. On the smooth high-altitude plateau, variations in accumulation were less pronounced. However, here the standard deviation exceeded 22% of the average accumulation rate. Provided that the snow radar soundings are supported by dating of reference horizons along the travel route, this is a good method to obtain the accumulation rate and pattern for large areas with a high spatial resolution.
Keywords: Dronning Maud Land; fysisk geografi; geofysikk; geokjemi; glasiologi; iskjerner

Spatial and temporal variation of sublimation on Antarctica: Results of a high-resolution general circulation model - van den Broeke, Michiel R. (Journal of Geophysical Research: Atmospheres, 1997)
In this paper we use output of a high-resolution general circulation model (ECHAM-3 T106, resolution 1.1°?1.1°) to study the spatial and temporal variation of sublimation on Antarctica. First, we compare model results with available observations of sublimation rates. The yearly cycle, with small latent heat fluxes during the winter, is well reproduced, and the agreement with sparsely available spot observations is fair. The model results suggest that a significant 10?15% of the annual precipitation over Antarctica is lost through sublimation and that sublimation plays an important role in the formation of blue ice areas. A preliminary analysis of the atmospheric boundary layer moisture budget shows that the spatial variation of sublimation in the coastal zone of East Antarctica can be explained by variations of horizontal advection of dry air. Dry air advection, and thus surface sublimation, is enhanced in areas where katabatic winds are strong and have a large downslope component and where the Antarctic topography drops suddenly from the plateau to the coastal zone. In areas where horizontal advection is small, like the plateau and the large ice shelves, special conditions must be met to make significant sublimation at the surface possible.
Publisher: John Wiley & Sons, Ltd
Keywords: Antarktis; atmosfæren; geofysikk; meteorologi

Modelling the ocean response to secular surface temperature transitions - Mork, K. A.; Skagseth, Øystein (Climate Dynamics, 1996)
The ocean response to surface temperature transients is simulated with the use of the Hamburg large-scale geostrophic (LSG) ocean general circulation model (OGCM). The transition, from the present to a climate corresponding to a doubling of the atmospheric CO2 content, is compared with the reversed transition. For the Atlantic, the time scale for the deep ocean to adjust to the temperature changes was similar for both transitions. In the Pacific, the time scale is shorter for the present to warm transition than for the reverse case, a result of increased production of Antarctic bottom water (AABW) during the warm climate. While the transition from cold to warm climate shows no secular variability, the reversed transition generates considerable variability on time scales of 300–400 years. For the warm climate, oscillations with periods of 45 years are found in the Southern Ocean. Results of principal oscillation pattern (POP) analysis indicate that these oscillations are due to interaction between convection in the Southern Ocean and advected salinity anomalies in the Antarctic Circumpolar Current (ACC) and the Southern Pacific Ocean.
Fulltext: https://www.researchgate.net/publication/225411625_Modelling_the_ocean_response_to_secular_surface_temperature_transitions
Keywords: AABW; Sørishavet; Sørishavsstrømmen; geofysikk; havstrømmer; oseanografi; vannmasser

A model of ice shelf-ocean interaction with application to the Filchner-Ronne and Ross Ice Shelves - Nøst, Ole Anders; Foldvik, Arne (Journal of Geophysical Research: Oceans, 1994)
A simple analytical model has been developed to study the formation of Ice Shelf Water (ISW). ISW is assumed to flow as a buoyancy-driven layer underneath the ice shelf. A relation between potential temperature and salinity in the ISW layer is calculated from the mass and energy balance. This temperature-salinity relation is shown to depend only on the temperature and the salinity of the source water mass and to be practically independent of entrainment and melt rates. The model results are obtained without making any assumptions about entrainment and melt rates. The model is in good agreement with observations under the Ronne Ice Shelf, and it indicates that ISW in the Filchner Depression is formed from Western Shelf Water (WSW) with salinity higher than 34.75 practical salinity units. Such high-salinity water is only observed in the Ronne Depression in the western part of the continental shelf. This implies a circulation of WSW, under the Filchner-Ronne Ice Shelf, from the Ronne Depression into the Filchner Depression. Similarly, the model shows that the ISW observed under J9 at the Ross Ice Shelf has been formed from Low Salinity Shelf Water (LSSW) from the eastern parts of the Ross Sea continental shelf. LSSW must therefore circulate under the eastern parts of the Ross Ice Shelf.
Keywords: Antarktis; geofysikk; isshelf; kontinentalsokkel; oseanografi

Radio-echo investigations in Dronning Maud Land - Kennett, Michael (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geofysikk; isshelf; isstrøm; klimaendringer

Oxygen 18 and helium as tracers of ice shelf water and water/ice interaction in the Weddell Sea - Schlosser, Peter; Bayer, Reinhold; Foldvik, Arne; Gammelsrød, Tor; Rohardt, Gerd; Münnich, Karl Otto (Journal of Geophysical Research: Oceans, 1990)
Oxygen 18 and helium isotope data from stations located in the Filchner Depression, on the continental slope of the southern Weddell Sea, and in the central Weddell Sea are presented and discussed. The 18O and 4He signals imprinted on the water circulating under the Filchner/Ronne Ice Shelf (Ice Shelf Water, or ISW) due to melting of glacial ice at the base of the ice shelf are traced across the sill separating the Filchner Depression from the Weddell Sea. Low δ18O values are correlated with high 4He concentrations in the ISW found in the Filchner Depression (minimum δ18O values: −0.8‰; maximum 4He concentrations: about 4.7×10−8 cm3 STP g−1). The fraction of glacial meltwater contained in the ISW found in the Filchner Depression is estimated to about 6 to 7‰. The 18O and helium isotope data from the overflowing shelf water component observed on the continental slope confirm the hypothesis that ISW contributes significantly to the Weddell Sea Bottom Water (WSBW). On the basis of a inultiparameter water mass analysis it is discussed which fraction of the WSBW originates from ISW and which other shelf waters potentially could contribute to WSBW.
Keywords: Sørishavet; Weddellhavet; brehylle; geofysikk; hydrografi; isbrem; isshelf; oseanografi; smeltevann; vannmasser